Identification of cellular factors associated with inflammation and neurodegeneration in multiple sclerosis - Rodero-Romero, Alexander; Fernández-Velasco, José Ignacio; Monreal, Enric; Sainz-Amo, Raquel; Álvarez-Lafuente, Roberto; Comabella, Manuel; Ramió-Torrentà, Lluís; García-Domínguez, José M.; Villarrubia, Noelia; Sainz de la Maza, Susana; Domínguez-Mozo, María; Quiroga-Varela, Ana; et al. (Frontiers in Immunology, 2025)
BackgroundSerum biomarkers as neurofilament light chain (sNfL) and glial fibrillary acidic protein (sGFAP) enabled early identification of multiple sclerosis (MS) patients at risk of relapse-associated worsening (RAW) or progression independent of relapses (PIRA). However, the immunological mechanisms underlying these clinical phenotypes remain unclear.MethodsWe conducted a cross-sectional study including 117 MS patients and 84 healthy controls (HC). Patients were stratified as NLGL (low sNfL and sGFAP), NH (high sNfL at different levels of sGFAP), and NLGH (low sNfL and high sGFAP). Percentages of blood and cerebrospinal fluid (CSF) mononuclear cells, and intracellular production of cytokines by T and B cells after “in vitro” stimulation were analyzed by flow cytometry.ResultsWe identified a common inflammatory profile present in the blood of all MS groups comprising significant increases of effector CD4+ and CD8+ T cells, of memory and antigen-presenting B cells, of CD4+ and CD8+ T cells producing interferon-gamma, interleukin-17 and tumor necrosis factor-alpha (TNF-α) and of B cells producing TNF-α. Additionally, the highly inflammatory NH group showed lower frequencies of different regulatory subsets (transitional B cells, PDL1+ monocytes and Treg cells) compared to HC and increased percentages of CD4+ and CD8+ T cells producing granulocyte-macrophage colony-stimulating factor and of effector CD56dim NK cells. They also showed lower percentages of Treg in blood and CSF compared to the low inflammatory NLGL group, which also displayed higher frequencies of regulatory CD56dim, NKG2A+ cells.ConclusionAll MS patients share increased inflammatory B and T cells, but differ in regulatory or NK subsets, which identify highly inflammatory or benign disease courses.